A review: influence of the sow’s parity on farrowing and neonate performance - Corrales-Hernández, Adrián Alejandro; Roldán-Santiago, Patricia; Bonilla-Jaime, Herlinda; De la Cruz-Cruz, Luis Alberto; Limón-Morales, Ofelia; Orozco-Gregorio, Héctor; Pineda-Reyes, Raym (Frontiers in Animal Science, 2025)
Several authors have noted that a sow’s parity has a significant impact not only on her own productivity but also on the performance of her piglets. Analyzing all the factors related to sows and their neonates at each birth event is an effective tool for improving management and reproductive performance on production units. Multiparous sows exhibit cortisol levels up to 38% higher than those of primiparous sows at peripartum, but the latter have prolactin levels 54-70% lower that reduce colostrum production. In addition, the weaning-to-estrous period is 3 days longer in primiparous sows, and their farrowing intervals up to 8 days longer. Farrowing performance is significantly affected, as litter size tends to increase in multiparous sows, thus extending duration. Piglets are also influenced by parity: those born to multiparous sows have higher weights, up to 2.21 kg more in total litter weight (up to 200 g/piglet). Their thermoregulation capacity is better as they show temperatures up to 1.6°C higher, greater overall vitality, and higher growth rates than the neonates of primiparous sows, which also suffer higher mortality rates. Given the obvious performance differences among sows of different parity and their offspring, swine breeders must determine the precise effects of this factor. This review details the key differences related to parity in the events surrounding farrowing in sows and the early lives of their offspring.